Cloning and characterisation of an endosperm specific glutelin B1 promoter from Sri Lankan rice (Oryza sativa L. ssp. indica) variety Bg 250 - Kajendran, K; Chandrasekharan, N. V; Hettiarachchi, C. M; Nanayakkara, A. K; Elvitigala, D. A. S; Wijesundera, W. S. S. (My University, 2019)
Glutelins are the primary source of energy storage in the endosperm of rice grains. Among the glutelin promoters, Glutelin B-1 (GluB-1) is widely studied and used in transgenic rice plants to express recombinant proteins in the endosperm. In this study, three regions: 350 bp, 1308 bp and 2300 bp of the GluB-1 promoter were PCR amplified from the genomic DNA of Bg 250 rice variety. The amplified fragments were cloned into pGEM®-T Easy vector for characterisation of GluB-1 promoter. Each region of GluB-1 promoter was separately cloned into the promoterless binary vector pCAMBIA1391Z harbouring the β-glucuronidase (GUS) reporter gene. Putative transgenic plants were generated by Agrobacterium-mediated gene transformation and confirmed by PCR using nopaline synthase terminator primers. All GluB-1 promoter constructs showed expression of the GUS gene in the endosperm of T0 transgenic plant seeds. The 1308 bp GluB-1 promoter revealed the highest expression as determined by the GUS assay. This indicates the potential of this promoter for expression of recombinant proteins in rice endosperm.
Keywords: GluB-1 promoter; transgenic rice